Preparation and characterization of mesoporous activated carbons from waste tyre - Song, X. H. (2013)
Mesoporous activated carbon was prepared from waste tyres via acid wash and steam activation. The effect of synthetic conditions was studied and the surface texture of the tyre carbon was characterized. The optimally obtained carbon sample presents a surface area of ∼1200 m2 g−1 and is predominantly mesoporous. Acid wash was found to play an important role in the structural development of carbon. The advantage of the mesoporous carbon was demonstrated by its excellent sorption capacity towards the bulky molecule of a basic dye (methylene blue).